2018
DOI: 10.1097/ccm.0000000000003218
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Post-Intensive Care Syndrome Problems Among 406 Survivors of Critical Illness*

Abstract: In this multicenter cohort study, one or more post-intensive care syndrome problems were present in the majority of survivors, but co-occurring problems were present in only one out of four. Education was protective from post-intensive care syndrome problems and frailty predictive of the development of post-intensive care syndrome problems. Future studies are needed to understand better the heterogeneous subtypes of post-intensive care syndrome and to identify modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
364
4
27

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 392 publications
(415 citation statements)
references
References 36 publications
20
364
4
27
Order By: Relevance
“…One Australian study showed that more than 50% of patients discharged from the ICU had developed ICU-acquired weakness, which was associated with death between ICU discharge and day 90 (TEAM Study Investigators, 2015). Early mobilisation is associated with more delirium-free days and improved cognitive outcome after ICU discharge (Devlin et al, 2018 (Berntzen et al, 2018;Cutler, Hayter, & Ryan, 2013;Laerkner et al, 2017;Marra et al, 2018). We still lack a systematic approach to help manage the discomfort described by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…One Australian study showed that more than 50% of patients discharged from the ICU had developed ICU-acquired weakness, which was associated with death between ICU discharge and day 90 (TEAM Study Investigators, 2015). Early mobilisation is associated with more delirium-free days and improved cognitive outcome after ICU discharge (Devlin et al, 2018 (Berntzen et al, 2018;Cutler, Hayter, & Ryan, 2013;Laerkner et al, 2017;Marra et al, 2018). We still lack a systematic approach to help manage the discomfort described by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond cognitive impairment, mental and physical health are often also impaired after ARDS and critical illness, more generally (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Mental health issues include depression, anxiety, and/or post-traumatic stress disorder.…”
Section: Morbidity Of Ards Survivorsmentioning
confidence: 99%
“…Mental health issues include depression, anxiety, and/or post-traumatic stress disorder. Functional impairment and physical decline are common after ARDS (22)(23)(24)(25). Specifically, two of three ARDS survivors experience difficulty with activities of daily living such as: using the telephone, shopping, preparing meals, doing housework, laundering clothes, utilizing transportation, taking medications, and/or money management (26).…”
Section: Morbidity Of Ards Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we have demonstrated that a lower-dose subchronic systemic immune challenge results in memory deficits that emerge and persist at least three months after the end of the immune challenge (Tchessalova and Tronson, 2019). These long-lasting memory deficits are likely mediated by changes in neuroimmune and neuronal function that persist long after immune activation and likely contribute to cognitive decline, affective dysregulation, and increased risk of dementia and Alzheimer's disease long after recovery from major illnesses including sepsis and heart attack (Semmler et al, 2007;Gharacholou et al, 2011;Marra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%